Autonomy-Supportive Faculty, Students' Self-System Processes, Positive Academic Emotions, and Agentic Engagement: Adding Emotions to Self-System Model of Motivational Development - Bordbar, Maryam (Frontiers in Psychology, 2021)
Autonomy-Supportive Faculty, Students’ Self-System Processes, Positive Academic Emotions, and Agentic Engagement: Adding Emotions to Self-System Model of Motivational Development